An unusual cause of acute abdomen: Mesenteric heterotopic pancreatitis causing confusion in clinical diagnosis - Hakan CANBAZ; Tahsin ÇOLAK; Duygu DÜŞMEZ APA; Orhan SEZGİN and Süha AYDIN (Turkish Journal of Gastroenterology, 2019)
-